Odpowiedzi

  • Użytkownik Zadane
2010-01-25T19:41:41+01:00
A)(x-2)-(2-x) = x-2-2+x = -4
b)(a+b)+(2a-b)-(a-2b) = a+b+2a-b-a+2b = 2a + 2b
c)(3x-y+1)-(x+y)+(y-x) = 3x-y+1-x-y+y-x = x + 1 - y
d)-(2a² - 3ab)-(2b-3a²)+(-ab-b) = -2a²+3ab-2b-3a²-ab-b = -5a²+ 2ab - b
2010-01-25T19:44:07+01:00
A x-2-2+x=2x-4
b a+b+2a-b-a+2b=2a+2b
c 3x-y+1-x-y+y-x=x-y+1
d -2a<kw>+3ab-2b+3a<kw>-ab-b=a<kw>2ab-b
Najlepsza Odpowiedź!
2010-01-25T19:45:44+01:00
A)2x-4
b)2a+2b
c)2x-2y+1+y-x=x-y+1
d)-(2a² - 3ab)-(2b-3a²)+(-ab-b)=-2a²+3ab-2b+3a²-ab-b=a²+2ab-3b